Ograniczanie ryzyka w planowaniu produkcji rodzinnych gospodarstw rolnych - Karmowska, Grażyna (Restriction of Risk in Family Households Production Planning, 2005)
The purpose of this elaboration is to show the possibilities of mathematical modelling usage in the risk including production planning. Economical risk is understood as probability of wastage of for seen or expected economical and financial outcome, connected with business or decisions that have been taken. Family household is treated like the company in which you create production planning. This plan should allow reduction of negative risk effects of agricultural production, and also it should improve household efficiency. In such a purpose MOTAD model was used and compared to classical line model. Methods of one year plan modelling in family households while regarding risk have great practical use. Improvement of this methods can be used in advising as an assistance when taking decisions. While applying MOTAD model to identify the risk, there have been designated few plan models while taking into account farmers aversion to risk.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 405-411